Batch versus Flow Photochemistry: A Revealing Comparison of Yield and Productivity. Issue 46 (26th September 2014) - Elliott, Luke D.; Knowles, Jonathan P.; Koovits, Paul J.; Maskill, Katie G.; Ralph, Michael J.; Lejeune, Guillaume; Edwards, Lee J.; Robinson, Richard I.; Clemens, Ian R.; Cox, Brian; Pascoe, David D.; Koch, Guido; et al.
Abstract The use of flow photochemistry and its apparent superiority over batch has been reported by a number of groups in recent years. To rigorously determine whether flow does indeed have an advantage over batch, a broad range of synthetic photochemical transformations were optimized in both reactor modes and their yields and productivities compared. Surprisingly, yields were essentially identical in all comparative cases. Even more revealing was the observation that the productivity of flow reactors varied very little to that of their batch counterparts when the key reaction parameters were matched. Those with a single layer of fluorinated ethylene propylene (FEP) had an average productivity 20 % lower than that of batch, whereas three‐layer reactors were 20 % more productive. Finally, the utility of flow chemistry was demonstrated in the scale‐up of the ring‐opening reaction of a potentially explosive [1.1.1] propellane with butane‐2, 3‐dione.